Udział opozycji w realizacji funkcji ustawodawczej w Sejmie VII kadencji - Łabędź, Krzysztof (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
The text describes parliamentary opposition participation in the legislative activity of the Sejm of the 7th term. An attempt has been made to answer the question, to what extent the opposition had an impact on the shape of legislation and whether it really could benefit from existing opportunities. The analysis has been based primarily on quantitative indicators illustrating the method of voting of opposition groupings on draft laws prepared by the government and MPs of the ruling coalition. As a result, there have been obtained patterns of the most common voting methods of opposition groupings and data that allow ordering them from the most to the least opposition. In addition, another conclusion is the fact that in the majority of cases, the majority of votes of the ruling coalition was ultimately decisive.
Participation of the opposition in realizing the legislative function in the Sejm of the 7th term
Keywords: Parliamentary opposition; Sejm of the 7th term; legislative function; method of voting